The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/mrc.2268
|View full text |Cite
|
Sign up to set email alerts
|

On the unusual2Jcoupling dependence onsyn/antiCHO conformation in 5‐X‐furan‐2‐carboxaldehydes

Abstract: A remarkable difference for (2)J(C(2)-H(f)) coupling constant in syn and anti conformers of 5-X-furan-2-carboxaldehydes (X = CH(3), Ph, NO(2), Br) and a rationalization of this difference are reported. On the basis of the current knowledge of the Fermi-contact term transmission, a rather unusual dual-coupling pathway in the syn conformer is presented. The additional coupling pathway resembles somewhat that of the J(H-H) in homoallylic couplings, which are transmitted by hyperconjugative interactions involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
4
8
0
Order By: Relevance
“…It is seldom observed that a negative hyperconjugative interaction33 takes place for a synperiplanar configuration between a lone pair and an antibonding orbital. Similar interactions were discussed for 2 ‐CHO‐pyridine,34 and furfural 35. Doubtless, the ‘acetaldehyde effect’ is one of the main effects leading to the differences between 2 J C 3 H 2 and 2 J C 2 H 3 SSCCs in furan ( 1a ) and in pyridine ( 2b ), since in both cases only the former SSCC is contributed to by that effect.…”
Section: Fc Term For Ssccmentioning
confidence: 54%
“…It is seldom observed that a negative hyperconjugative interaction33 takes place for a synperiplanar configuration between a lone pair and an antibonding orbital. Similar interactions were discussed for 2 ‐CHO‐pyridine,34 and furfural 35. Doubtless, the ‘acetaldehyde effect’ is one of the main effects leading to the differences between 2 J C 3 H 2 and 2 J C 2 H 3 SSCCs in furan ( 1a ) and in pyridine ( 2b ), since in both cases only the former SSCC is contributed to by that effect.…”
Section: Fc Term For Ssccmentioning
confidence: 54%
“…[20 -22] Since many years ago, it is known that the FC term can be transmitted by an intermediate moiety, [23,24] like for instance, that suggested by Mallory et al, [25] in which a coupling 6 J F -F = 6.4 Hz is transmitted through a phenyl ring. A recently reported unusual case is that of the stereo-chemical dependence of the 2 J CH coupling involving the formyl proton in several 5-X-furfurals [26] where an FC pathway involving the overlap between the lone-pairs of both oxygen atoms is activated for the syn but not for the anti conformations.…”
Section: Coupling Constants Chemical Shifts and Preferred Conformationsmentioning
confidence: 98%
“…In fact, in his equation, he included an additional sin(2y) term to improve the fitting. It was later utilized also by Altona [14,16] and in more recent studies [87,[91][92][93][94][95][96][97] particularly devoted to carbohydrates. In ordinary proteins, asymmetry is expected in coupling constants 3 3 J(N,C g ), and 3 J(C 0 ,C g ), which are governed by the dihedral angle w related to the amino acid side-chain torsion [83].…”
Section: J-coupling Dependence Upon Dihedral Angles 31 Analytic Expmentioning
confidence: 99%
“…In this sense, exploring the dependence of a given J-coupling over the entire range of values of the corresponding dihedral angle can be better achieved using ab initio calculations [24,80,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104]107,[111][112][113][114][115][116][117][118][119][120][121][122][123]. Whether or not the associated Karplus fit will improve over the empirical ones for structure determination critically depends on the ability of the computational model (i.e.…”
mentioning
confidence: 99%